Authorization of attributes; its origin and factors of survival and extension - Attia, Somaya Mohamed (Journal of Islamic Sciences, 2019)
The study aimed to clarify the issue of delegation in names and attributes and its origin and the reasons for its extension. The study followed the descriptive, analytical, analytical approach to written documents, which includes a total of sayings of Islamic scholars in the past and present, and the research may be from an introduction, two chapters and a conclusion; And in it two topics; the first: the definition of the mandate language and terminology, while the second: the origin and development of the mandate, and the second chapter included the causes and factors of extension until the present era, and the results revealed the following: - The truth of the delegation: It is a negation of the attributes of God Almighty, and it is contrary to the method of the companions and the predecessor of the nation, where they believed in the qualities abstract from the meanings, until they became the matter to disable these attributes, as they disrupted the texts in which the attributes were mentioned, because they became the result of saying texts meaningless , And nobody understands it from creation. Several factors have helped to perpetuate the doctrine of authorization. Including: the extension of the Ash’ari school of thought, whose authorization is one of its ways with the other way of interpretation, and their apprehension to the public that the mandate is the doctrine of the predecessor, in addition to the occurrence of some imams and the people of hadith in saying authorization, which contributed to the consolidation of the doctrine of authorization, and its survival in their books that contemporaries still infer Out on his health. Based on the results, a number of recommendations and proposals aimed at correcting the belief and showing the error of violators were presented.